Economic growth and the concept of diminishing marginal governance effect. Issue 4 (5th August 2019) - Briguglio, Lino Pascal; Vella, Melchior; Moncada, Stefano
Abstract : Purpose: The purpose of this paper is to examine whether good governance across countries, utilising the Rule of Law indicator of the Worldwide Governance Indicators, is associated with economic growth, measured in terms of real GDP. It is to be noted that in this paper both variables are measured in terms of changes, comparing like with like. It is hypothesised that a country with a high level of economic development and a high level of good governance (typically an economically advanced country) tends to find it more difficult to improve these two variables, when compared to a country with lower levels GDP per capita and good governance (typically an economically backward country). This assumption is termed the "diminishing marginal governance effect". Design/methodology/approach: The paper tests the hypothesis that governance improvements are related to real GDP growth, using the panel data regression approach. In this way both variables are measured in terms of changes, comparing like with like. Relevant control variables are utilised to impose the ceteris paribus condition. Findings: The paper finds that improvements in good governance are statistically and significantly related to economic growth. This confirms the hypothesised "diminishing marginal governance effect" explained above. Research limitations/implications: The main research limitation of this paper is that measuring changes in the "Rule of Law" indicator over time may be subject to errors given that the "Rule of Law" score of each year is an average value with related standard deviations, and the latter vary from one year to another and from one country to another. Practical implications: The major practical implication of this paper is that good governance matters for economic growth and that in order to produce evidence for this the governance score must be measured in terms of changes and not in terms of levels. Another implication is that equations that compare economic growth with levels of governance are misspecified as they would not be comparing like with like. Social implications: There are various beneficial social implications associated with good governance which is considered as a major pillar for orderly social relationships. Economic growth also has important social implications as it means, if properly distributed, improvements in material well-being of the population. Originality/value: The originality of this paper is that it measures governance in terms of changes and not of levels. Studies on the relationship between governance and economic growth that measure governance in terms of levels generally do not find a positive relationship between the two variables. In using changes in both governance and real GDP, this paper confirms the "diminishing marginal effect of governance", hypothesis.